Health Needs Assessment among Female Adolescents: A Case Study from Iran - Nahid Khoshnoudfar; Mohammad-hasan Imani-Nasab; Mehdi Birjandi; Maryam Khoshnoudfar; Shadi Abdi; Soraya Nouraei Motlagh (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Identification of health needs of female adolescents is a necessity due to their double roles in the health status of current and future generations. Aim: To assess various types of health needs in physical, mental-emotional, social, spiritual, and educational aspects among Iranian female adolescents. Materials and Methods: A total of 400 girls studying in high schools of Khorramabad city of Iran, were selected using the stratified sampling and multistage cluster sampling. The tool used for data collection was Female Adolescents' Health Needs questionnaire. SPSS Version 20 Software was used to analyse the obtained data via Pearson correlation coefficient, ANOVA, and t-test. Results: The mean score and the Standard Deviation (SD) of the girls' health needs were 89.79±11.47. The highest and lowest health needs were spiritual and educational needs with the average scores of 94.79±11.70 and 87.37±14.13, respectively. The correlation coefficient test indicated that there is a strong and significant correlation between different dimensions of female adolescents' health needs. Social (75%) and spiritual (65%) dimensions had the highest and the lowest correlations with other dimensions, respectively. Conclusion: The study results show that the girls had varied health needs. To be prioritized are spiritual health, physical health, social health, mental-emotional health, and educational health, as found in this study.